Advanced Microsystems for Automotive Applications 2014 Smart Systems for Safe, Clean and Automated Vehicles - Fischer-Wolfarth, Jan; Meyer, Gereon (Lecture Notes in Mobility, 2014)
The automobile is going through the biggest transformation in its history. Automation and electrification of vehicles are expected to enable safer and cleaner mobility. The prospects and requirements of the future automobile affect innovations in major technology fields like driver assistance systems, vehicle networking and drivetrain development. Smart systems such as adaptive ICT components and MEMS devices, novel network architectures, integrated sensor systems, intelligent interfaces and functional materials form the basis of these features and permit their successful and synergetic integration. It has been the mission of the International Forum on Advanced Microsystems for Automotive Applications (AMAA) for more than fifteen years to detect novel trends and to discuss the technological implications from early on. Therefore, the topic of the AMAA 2014 will be â_oSmart Systems for Safe, Clean, and Automated Vehiclesâ__.Â This book contains peer-reviewed papers written by leading engineers and researchers which all address the ongoing research and novel developments in the field.